Emerging programs for autism spectrum disorder : improving communication, behavior, and family dynamics - Papaneophytou, Neophytos; Das, Undurti N. (London: Academic press, 2021)
"Emerging Programs for Autism Spectrum Disorder: Improving Communication, Behavior, and Family Dynamics brings forward a hybrid and a transdisciplinary methodology to identify methods used to diagnose, treat, and manage those with autism within personal and social constructs and values building exemplary international experiences from across the globe. Luminary experts offer their superb level of expertise through their research, experience, and clinical work. The book addresses all the aspects of care, lifespan, and lifestyle issues from treatment to living. It will emphasize issues related to neurodiversity, individuality, best practices, and support of people on the Autism Spectrum and their families. In addition, this book includes specific case studies, highlighting family experiences and the application of best practices by therapists thereof"--
Minimal Level Cataloging Plus.
Includes bibliographical references and index.
Keywords: Autism spectrum disorders; Autism